Pupuk Hayati Cendawan Mikoriza Arbuskula (CMA) dapat Mengefisienkan penggunaan Pupuk NPK Terhadap Pertumbuhan dan Produksi Tanaman Bawang Merah (Allium aslonicum L.) - Samah, Eri; Linda Br Jabat, Yelfi Yana; Hulu, Iman Berkat (UNIVERSITAS LABUHANBATU, 2025)
This study aimed to investigate the effect of arbuscular mycorrhizal fungi (AMF) and NPK fertilizer, both individually and in combination, on the growth and yield of shallot (Allium ascalonicum L.). The experiment was conducted using a Randomized Complete Block Design (RCBD) with two factors: AMF (0, 5, 10, and 15 g/plant) and NPK fertilizer (0, 15, 30, and 45 g/plot), each replicated three times. Observed parameters included plant height, number of leaves per plant, number of bulbs, bulb diameter, and fresh bulb weight. Data were analyzed using ANOVA and further tested with Duncan’s Multiple Range Test (DMRT) at a 5% significance level. The results showed that the interaction between AMF and NPK fertilizer had no significant effect on all observed parameters. However, certain combinations such as 10 g AMF with 30 g NPK and 15 g AMF with 30 g NPK tended to yield higher averages in bulb number and weight compared to single treatments. The use of AMF has potential to improve nutrient uptake efficiency and support more sustainable shallot cultivation. Keywords: shallot, arbuscular mycorrhizal fungi, NPK fertilizer, growth, yield